Rede de articulação ensino-serviço na saúde - RAESS - Gonçalves, Ana Camila; Lima, Claudia Feio da Maia; Magalhães, Carolina Gusmão; Prazeres, Carolina; Santos, Delma Alves dos; Pereira, Érica Cardoso Firmino; Santos, Queli Nascimento; Assis, Ivonete de Jesus; Santos, Simone Andrade dos; Barbosa, Deise Santana de Jesus (Revista Acadêmica GUETO, 2024)
Projeto